In-war electronic financial securities: military bonds [Articol] - Halak, Anastasiia; Kiriiak, Oksana (CEP USM, 2024)
War in the 21st century, in a democratic world, requires modern ways of maintaining people’s livelihoods. Maintaining economic stability is an important component for this. We strive for Ukrainians to develop a culture of managing their own funds, to be able to use financial instruments for the benefit of their wallets and state interests, in particular, by buying military bonds that finance the military needs of the budget. A citizen immediately understands where and for what money is directed. After all, in the conditions of war, it is primarily the provision of the army - salaries for military personnel and medics, purchase of weapons, body armor, ammunition, etc. Military bonds are investments in the victory of Ukraine, at the same time, you get a guaranteed profit. Military bonds are securities issued by the state during martial law. They have become an effective tool for supporting the economy of Ukraine and the Armed Forces. Funds for them are returned to the eSupport card after 3, 6, 12 or more months. It depends on the payment date and the term of the bonds.
Keywords: military bonds; securities; war; bank; broker